Let P(n) be the statement “(n^3)-n is divisible by 3”
First we’ll examine the base case: P(1)
(n^3)-n=1^3-1=1-1=0
0=3*0, so is divisible by 3, and so P(1) is true
Now assume for some k>0, an integer, that P(k) holds true, i.e. there exists an integer a such that (k^3)-k = 3a.
We want to show that this implies that P(k+1) is true:
(k+1)^3-(k+1)
=k^3+3k^2+3k+1-k-1 (This is just a binomial expansion)
=k^3-k +3k^2+3k (The 1’s cancel. Since we want to use our assumption we put k^3-k together)
=3a+3k^2+3k (Using the inductive hypothesis)
=3b (b is clearly an integer so we’re done)
Now since we’ve shown that P(n) holds for n=1 and that P(k) implies P(k+1), then by mathematical induction it follows that P(n) is true for all integers n>0. q.e.d.
5065 Views
See similar Further Mathematics A Level tutors